Guidelines for preventing water contamination during Mughal reign: A specialized study of Al-Fatawa al-’Alamgiri: مغل دورِ حکومت میں آبی آلودگی کی روک تھام سے متعلق ہدایات : فتاوی عالمگیری کا اختصاصی مطالعہ - Ilahi, Mahboob; Haq, Dr. Saeed Ul (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Water is a blessing from ALLAH. It is a symbol of life, and religious precepts encourage people to safeguard water. In different eras, Muslim rulers performed an excellent job of protecting and conserving water, particularly in terms of environmental pollution. The Mughal era was particularly prosperous in this sense. Environmental pollution regulation was enacted during the Mughal Empire, particularly during the reign of Emperor Aurangzeb, and significant progress was made. During this reign, work on jurisprudence editing was undertaken, and in the early time, a full and authentic book on Islamic jurisprudence was published in order to settle issues and difficult problems in accordance with Islamic Shariat. It is referred to as Al-Fatawa al-'Alamgiri in the Arab world known as Al-Fatawa al-Hindiyya. The main guidelines for water conservation are discussed in this book, among other regulations and legislation. In this study, we will provide an analytical evaluation of such norms and regulations.